Choice in Learning: Differentiating Instruction in the College Classroom - Angela Danley; Carla Williams (InSight, 2020)
This article addresses the importance of differentiated instruction in the college classroom. Additionally, it focuses on the results of the students’ perceptions of differentiated instruction in the college classroom. Students in the college classroom were given choice boards to display their understanding on phonemic awareness, phonics, and morphology. The article discusses ideas for future direction based on the results from the action research project.